Trust in the Time of Corona - Tilman Brück; Neil T.N. Ferguson; Patricia Justino; Wolfgang Stojetz (Institute of Labor Economics (IZA), 2020)
The global spread of COVID-19 is one of the largest threats to people and governments since the Second World War. The on-going pandemic and its countermeasures have led to varying physical, psychological, and emotional experiences, shaping not just public health and the economy but also societies. We focus on one pillar of society—trust—and explore how trust correlates with the individual experiences of the pandemic. The analysis is based on a new global survey—'Life with Corona'—and uses simple correlational statistics. We show that those who have had contact with sick people and those that are unemployed exhibit lower trust in people, institutions, and in general. By contrast, no such differences exist for those who have personally experienced symptoms of the disease. These associations vary across contexts and are not driven by concerns about personal health or the health of loved ones, but rather by increased levels of worry and stress. Our findings suggest that the effects of the pandemic go well beyond immediate health concerns, leading to important normative changes that are likely to shape how societies will emerge from the pandemic
Keywords: D91; I12; I31; O12; 330; COVID-19; coronavirus; pandemic; survey data; trust; well-being